PERAN KUALITAS KERJA DAN PELAYANAN KARYAWAN TERHADAP KEPUASAN PELANGGAN CV. PARE CENTER KEDIRI - Widyatmoko Widyatmoko; Dibyo Adi Wibowo (Jurnal Inovasi Penelitian, 2020)
The role of quality work and good employee service to the maximum, the company will get more new customers whose goal is to get profits for the company. Satisfaction that can be obtained from customers has a sense of pleasure or displeasure with the performance of employees in order to serve in the field of trading services. So that the achievement of customer satisfaction can be maximized and according to expectations for all, the purpose of this research is to obtain information about what influence the quality of employee performance and service has on customer satisfaction. The method used in analyzing the data is descriptive data analysis. While the data sources are obtained from the main or main data sources and other supports, to collect data using populations and samples. The results of the implementation of the study illustrate that the quality of work is given a variable (X1), employee service is given a variable (X2). set at 5%. So it can be concluded that there is a positive influence or contribution between the quality of work and employee service on customer satisfaction.